FAKTOR-FAKTOR YANG MENYEBABKAN STRES KERJA PERAWAT YANG BERTUGAS DI RUANG BANGSAL PASIEN RUMAH SAKIT KHUSUS PONTIANAK - B31110138, Rezan Wardana (Jurnal Manajemen Update, 2013)
The purpose of this research is to know the factors that cause stress, nurses on duty personnel work in the Special Hospital Patient Ward Pontianak. As for the variables in this study i.e., excessive workload, stress or time pressure in the completion of tasks, role ambiguity (do more than one job at the same time), and the level of difficulty dealing with patients who are critical. The sample in this study was 30 people. To measure the variables used Likert-scale research, as well as using descriptive qualitative analysis using the criteria of classification is very good, good, good enough, not good, and not very well against the factors that cause stress, nurses work. The results of this study revealed that the level of work stress experienced by nursing personnel who served in the Special Hospital patient Ward Pontianak was at categories is quite high. Based on the results of the study found factors that cause work stress among nursing personnel variable excessive workload, the pressure or the pressure of time in completing tasks, role ambiguity, and the level of difficulty dealing with patients who are critical. Keywords : Working Stress Of Nurses, Who Served In The Ward Room Patient Specialty Hospital Of Pontianak